1959
DOI: 10.1017/s0079497x00016534
|View full text |Cite
|
Sign up to set email alerts
|

A Sample Analysis of British Middle and Late Bronze Age Material, using Optical Spectrometry

Abstract: Metallurgical analysis of prehistoric material has hitherto been concentrated on examination of early artifacts, presumably made from newly-won metal, which may therefore contain trace elements to indicate the sources and trade-routes of contemporary metal supply. The present study was undertaken to discover whether bronze artifacts from the British Middle and Late Bronze Age, when an important component of the bronzes produced must have been re-used metal, show nonetheless perceptible variations in metal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 0 publications
4
27
0
Order By: Relevance
“…This is broadly analogous to the results obtained from both the Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) and Iron Age (see below). This is broadly analogous to the results obtained from both the Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) and Iron Age (see below).…”
Section: The Origins Of Iron Age Copper Metallurgysupporting
confidence: 88%
See 2 more Smart Citations
“…This is broadly analogous to the results obtained from both the Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) and Iron Age (see below). This is broadly analogous to the results obtained from both the Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) and Iron Age (see below).…”
Section: The Origins Of Iron Age Copper Metallurgysupporting
confidence: 88%
“…While the results show some similarities with both Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) Northover (1984;1991a;1991b) who has analysed excavated material from a number of sites in southern Britain (eg. While the results show some similarities with both Late Bronze Age (Brown & Blin-Stoyle 1959;Northover 1982a) Northover (1984;1991a;1991b) who has analysed excavated material from a number of sites in southern Britain (eg.…”
Section: The Origins Of Iron Age Copper Metallurgymentioning
confidence: 52%
See 1 more Smart Citation
“…Eleven elements were measured and the results obtained are given in table 1 together with the corresponding analyses previously obtained by optical emission spectrometry (OES) and tabulated in Blin-Stoyle (1959). Cobalt was not determined by emission spectometry; zinc which is not listed in table 1 was found by Brown and Blin-Stoyle (1959) to be below their limit of O.Olo(, in all seven bronzes, and this agrees with the atomic absorption results which similarly showed that the zinc content was less than the limit of 0.02",, in each case. From the British Museum Research Laboratory (BMRL) and Brown and Blin-Stoyle (BBS) results the ratios BMRLiBBS for each pair was calculated and the mean ratio (Z), standard deviation (a) and relative standard deviation (100a/2) for each element are listed at the foot of table 1.…”
Section: Atotnic Absorption Analysessupporting
confidence: 81%
“…
IntroductionA study of major importance for our understanding of the composition of bronze artefacts of the Middle and Late Bronze Ages in Britain is the group of 438 analyses carried out by optical emission spectrometry by Brown and Blin-Stoyle (1959). Their description of the project and its conclusions were presented in that paper, and in a subsequent paper by Blin-Stoyle (1 959) the full analytical results for nine elements were published together with a comprehensive description of the emission spectrometry procedure which followed.
…”
mentioning
confidence: 99%